Empathy: Assessment Instruments and Psychometric Quality – A Systematic Literature Review With a Meta-Analysis of the Past Ten Years - Lima, Felipe Fernandes de; Osório, Flávia de Lima (Frontiers in Psychology, 2021)
Objective: To verify the psychometric qualities and adequacy of the instruments available in the literature from 2009 to 2019 to assess empathy in the general population. Methods: The following databases were searched: PubMed, PsycInfo, Web of Science, Scielo, and LILACS using the keywords “empathy” AND “valid∗” OR “reliability” OR “psychometr∗.” A qualitative synthesis was performed with the findings, and meta-analytic measures were used for reliability and convergent validity. Results: Fifty studies were assessed, which comprised 23 assessment instruments. Of these, 13 proposed new instruments, 18 investigated the psychometric properties of instruments previously developed, and 19 reported cross-cultural adaptations. The Empathy Quotient, Interpersonal Reactivity Index, and Questionnaire of Cognitive and Affective Empathy were the instruments most frequently addressed. They presented good meta-analytic indicators of internal consistency [reliability, generalization meta-analyses (Cronbach’s alpha): 0.61 to 0.86], but weak evidence of validity [weak structural validity; low to moderate convergent validity (0.27 to 0.45)]. Few studies analyzed standardization, prediction, or responsiveness for the new and old instruments. The new instruments proposed few innovations, and their psychometric properties did not improve. In general, cross-cultural studies reported adequate adaptation processes and equivalent psychometric indicators, though there was a lack of studies addressing cultural invariance. Conclusion: Despite the diversity of instruments assessing empathy and the many associated psychometric studies, there remain limitations, especially in terms of validity. Thus far, we cannot yet nominate a gold-standard instrument.